Spirulina maxima extract prevents cell death through BDNF activation against amyloid beta 1-42 (Aβ1-42) induced neurotoxicity in PC12 cells. (23rd April 2018) - Koh, Eun-Jeong; Kim, Kui-Jin; Choi, Jia; Kang, Do-Hyung; Lee, Boo-Yong
Highlights: SM70EE, C-PC, and chlorophyll a reduce Aβ1-42 -induced neuronal cell death and PARP cleavage in PC12 cells. SM70EE, C-PC, and chlorophyll a attenuate oxidative stress by increasing anti-oxidant enzymes after in Aβ1-42-induced neurotoxicity in PC12 cells. SM70EE, C-PC, and chlorophyll a up-regulate BDNF in Aβ1-42 -induced neurotoxicity in PC12 cells. SM70EE, C-PC, and chlorophyll a inhibit APP processing in Aβ1-42 -induced neurotoxicity in PC12 cells. Abstract: Spirulina maxima is a blue-green micro alga that contains abundant amounts of proteins (60–70%), vitamins, chlorophyll a, and C-phycocyanin (C-PC). It has been shown to reduce oxidative stress, and prevent diabetes and non-alcoholic fatty liver disease. However, it is unclear whether Spirulina maxima 70% ethanol extract (SM70EE), chlorophyll a, and C-PC prevent Aβ1-42 -induced neurotoxicity in PC12 cells. The aim of this study was to investigate whether SM70EE, chlorophyll a, and C-PC prevent Aβ1-42 -induced cell death. SM70EE, chlorophyll a, and C-PC suppressed the Aβ1-42 -induced increase in poly-ADP ribose polymerase-1 (PARP-1) cleavage and reduced Aβ1-42 -induced decreases in glutathione and its associated factors. The level of brain-derived neurotrophic factor (BDNF), which plays a critical role in neuronal survival and neuroprotection, was increased by SM70EE, chlorophyll a, and C-PC in Aβ1-42 -treated cells. SM70EE treatment decreased oxidative stress and cell death in response to Aβ1-42 treatment, while simultaneously suppressing PARP cleavage and increasing the levels of glutathione (GSH) and its associated factors. Moreover, SM70EE lowered the levels of APP and BACE1, two major factors involved in APP processing, and increased BDNF expression during Aβ1-42 -induced neurotoxicity in PC12 cells. We suggest that SM70EE prevents cell death caused by Aβ1-42 −induced neurotoxicity via the activation of BDNF signaling.